Central retinal artery occlusion after catheter ablation of atrial fibrillation - Yasuhiro Matsuda (Clinical Case Reports, 2021)
Abstract Central retinal artery occlusion (CRAO) is a rare but severe and urgent complication of atrial fibrillation ablation. Awareness of this ophthalmologic complication and prompt treatment are needed because ischemic damage to the retina is irreversible from 4 hours after the onset of CRAO.